Chaos making a new science - Gleick, James (Abacus, a division of Little, Brown and Company (UK) Limited, 1993)
The author describes how scientists studying the growth of complexity in nature are discovering order and pattern in chaos. He explains concepts such as nonlinearity, the Butterfly Effect, universal constants, fractals, and strange attractors, and examines the work of scientists such as Mitchell J. Feigenbaum, Edward Lorenz, and Benoit Mandelbrot.